Pengaruh Leader Member Exchange Kepuasan Kerja Dan Karakteristik Individu Terhadap Kinerja Pegawai Pada Puskesmas Banda Sakti Lhokseumawe - Azhar Hasan; Melly Andriani; Likdanawati Likdanawati (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This study examined the effect of leader-member exchange, job satisfaction, and individual characteristics on employee performance at Banda Sakti Lhokseumawe Health Center. This study uses primary data obtained by distributing questionnaires to 63 respondents who were selected using the Proportional stratified random sampling technique. The data analysis method used is multiple linear regression analysis methods using SPSS 16.00 software. The results partially showed that the Leader-member exchange had a positive and significant effect on the performance of the Banda Sakti Lhokseumawe Health Center employees, Job satisfaction had a positive and significant effect on employee performance at Banda Sakti Lhokseumawe Health Center, Individual characteristics had a positive and significant effect on employee performance at the Banda Sakti Lhokseumawe Health Center. Simultaneously, Leader-Member Exchange, Job Satisfaction, and Individual Characteristics have a positive and significant effect on employee performance.